Role of ATM and PTEN in prostatic carcinogenic dog prostate: validation of aCGH results - Alves, Carlos Eduardo Fonseca [UNESP]; Pellicciari, Patricia Rosa [UNESP]; Rodrigues, Marcla Marcondes Pinto [UNESP]; Rogatto, Silvia Regina [UNESP]; Amorim, Renee Laufer [UNESP] (My University, 2013)
The canis lupus familiares is the only species besides human that spontaneously develop prostatic carcinoma (PCa). In addition, the metastatic sites are similar to those frequently reported in men. For these reasons, the dog is the best natural model to study the molecular mechanisms in PCa development providing a natural animal model for treatment by molecular targets. Previously, we investigated copy number alterations by arrayCGH (Canine Genome CGH Microarray 4x44K-G2519F, Agilent Technologies) in canine prostatic lesions: 3 benign prostatic hyperplasias (BPH), 4 proliferative inflammatory atrophies (PIA), and 14 PCa. Five histologically normal prostatic tissues were used as reference. Genomic alterations were evaluated using Genomic Workbench Standard Edition 5.0.14. This previous study revealed significant copy number losses of Atm and Pten exclusively in PCa. In the present study, ATM and PTEN immunoexpression were investigated using a tissue microarray (TMA) containing 149 canine prostatic paraffin-embedded lesions (BPH, PIA and PCa) collected from 67 animals. Immunohistochemical reactions were performed using the polyclonal rabbit antibody anti-PTEN (Santa Cruz Biotech, 1:50) and anti-ATM (Abcam, 1:50). The sections were developed with diaminobenzidine (DAB) and peroxidase. The immunohistochemical staining was assessed in each core by the distribution of positive cells for each antibody per lesion (score 1: <25% cells positive, 2: 26% to 50%, 3: being 51% and 75% and 4:> 75%) and intensity (1: weak, 2: moderate, 3: intense). Chi-square or Fisher exact test was used to determine the association between the categorical variables using GraphPad Prism 5 (GraphPad Software Inc., La Jolla, CA). Distribution of positive cells did not differ among lesions. PCa and PIA showed more samples with weak intensity for ATM when compared to normal prostatic tissue and BPH (PCa: p=0,032 and PIA: p=0,025). Benign prostatic hyperplasia and normal samples presented intense PTEN immunostaining than PCa (p=0,021) and PIA (p=0,0013). These results suggest that ATM and PTEN proteins expression in canine prostatic carcinoma are downregulated possibly by copy number losses. These findings are similar from those described in prostate carcinomas from human corroborating for the use of dogs as a natural model to study prostatic disease in men.